Repurposing PDE5-Inhibitors: Sildenafil Drives Arteriogenesis via Localized Regenerative Inflammation - Elbs, Katharina; Bobrowski, Lisa; Arnholdt, Christoph; Kübler, Matthias; Götz, Philipp; Rohrmoser, Michael R.; Merkus, Daphne; Lasch, Manuel; Deindl, Elisabeth (International Journal of Molecular Sciences, 2026)
Arteriogenesis, the growth of pre-existing arterioles into functional collateral arteries, represents a key adaptive response to severe arterial stenosis. This process is driven by hemodynamic forces and a tightly coordinated inflammatory cascade. Here, we investigated the effects of pharmacological stimulation of the nitric oxide-cyclic guanosine monophosphate (NO-cGMP) signaling pathway using the phosphodiesterase-5 (PDE5) inhibitor Sildenafil on collateral vessel growth in a murine model of femoral artery ligation (FAL). Flow cytometric analyses revealed that Sildenafil treatment significantly enhanced platelet–leukocyte aggregate formation, a prerequisite for the subsequent initiation of a localized perivascular inflammation. Histological and immunofluorescence analyses further demonstrated a marked increase in mast cell recruitment and degranulation at early time points (days 1 and 3 post-FAL). In addition, Sildenafil promoted perivascular macrophage accumulation on days 3 and 7, with a pronounced shift toward an M2-like pro-regenerative polarization state, ultimately resulting in the enhanced proliferation of vascular cells and the enlargement of collateral diameters. Together, these findings identify Sildenafil as a potent enhancer of arteriogenesis through coordinated immune cell activation, stimulating vascular cell proliferation along with positive collateral outward remodeling. Thus, Sildenafil emerges as a promising therapeutic candidate to promote collateral artery growth in cardiovascular occlusive diseases.
CRIS-Team Scopus Importer:2026-02-06
Keywords: cardiovascular occlusive disease; collateral artery growth; natural bypass growth; PDE5; PDE5-inhibitor; peripheral artery disease; platelet activation; regenerative inflammation; Sildenafil